Reversible Activation and Transfer of White Phosphorus by Silyl-Stannylene - Sarkar, Debotra; Weetman, Catherine; Munz, Dominik; Inoue, Shigeyoshi (Angewandte Chemie International Edition, 2020)
Use of a silyl supported stannylene (MesTerSn(SitBu3) [MesTer=2,6-(2,4,6-Me3C6H2)2C6H3] enables activation of white phosphorus under mild conditions, which is reversible under UV light. The reaction of a silylene chloride with the activated P4 complex results in facile P-atom transfer. The computational analysis rationalizes the electronic features and high reactivity of the heteroleptic silyl-substituted stannylene in contrast to the previously reported bis(aryl)stannylene.
CRIS-Team Scopus Importer:2020-12-25
Keywords: main group; P; reversible activation; small molecule activation; tetrylenes